Detection of QTLs controlling heading date in the process of rice development at two environments - BAO Jin-song; BAO Zhi-yi; HE Ping; ZHU Li-huang (浙江大学学报. 农业与生命科学版, 2002)
Heading date (HD) is a major determinant of the regional and seasonal adaptation of rice varieties. In order to elucidate the quantitative trait loci (QTL) for HD in the process of rice development, a doubled haploid (DH) population was employed to map QTLs controlling HD at different heading stages in two locations, Hainan (HN) and Hangzhou (HZ) in China. The results indicated that a total of 8 QTL were identified at two environments and seven stages which were located on chromosomes 1, 6, 8, 10 and 12. Two QTL, qHD-1-1 and qHD-12 could be detected at both environments, the others were only detected at one environment. One QTL in HN, qHD-10-1, exerted its effect during 75-85 DAG (days after germination) and could explain 19.6% of the total variation. A major QTL, qHD-8-1 in HZ, showed its effect during 80-90 DAG. The other QTL were only detected in one stage, such as qHD-6 and qHD-10-2 were both specific for 80 DAG in HN, while qHD-1-2 and qHD-8-2 were specific for 85 and 80 DAG in HZ, respectively. Based on the QTL mapping results, we proposed a QTL effect timing model for the HD-controlling QTLs.